"O fim da miséria é só um começo"? : noção de pobreza no discurso do Plano Brasil sem Miséria - Orth, Thiana (2015)
The theme of the research is the idea of poverty in the Brazilian social policy discourse, more specifically, it seeks to analyze how is the production of meanings about this notion in the institutional discourse of Brazil Without Poverty Plan, and its relationship (directions) with the journalistic discourse about the plan. The discursive materiality of the work will focus on three digital magazines published in Brazil Without Poverty Portal, in 2011-2014, as well as in speeches by the President of Brazil (Dilma Rousseff), on the occasion of the launch of the plan in June 2011 and the announcement of new measures in February 2013. Furthermore, the editorial of two portals will be analyzed, the G1, linked to Globo and Carta Maior, linked to social movements, in order to observe the imaginary formations on which they are supported. The corpus of the research also covers news circulated in these portals about the launch of the plan in order to grasp the discursive game between the portals and the socio-historical and ideological determinations of the reported facts. It starts with the understanding of the historical production process of discourses coping with poverty from other modes of sociability, passing by discourses engendered by multilateral organizations, reaching the contemporary Brazilian social policies and the prevalence of Income Transfer Programs. It is through the Theory of Discourse Analysis proposed by Pêcheux (1969) and the construction of its own analytical device, which result analyzes of the thesis, which outline the Formation Discourse Neodesenvolvimentista (NDF) and the positions subject- Economicist and Conservadorist as dominants in the institutional discourse analysis.